To factor the expression \( x^3 + 125y^3 \), we recognize that it can be expressed as a sum of cubes. The formula for factoring a sum of cubes is:
\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \]
In this case, we can identify \( a = x \) and \( b = 5y \) since \( 125y^3 = (5y)^3 \).
Using the formula, we get:
-
Calculate \( a + b \): \[ x + 5y \]
-
Calculate \( a^2 \): \[ x^2 \]
-
Calculate \( ab \): \[ x \cdot 5y = 5xy \]
-
Calculate \( b^2 \): \[ (5y)^2 = 25y^2 \]
Substituting these into the formula yields:
\[ x^3 + 125y^3 = (x + 5y)(x^2 - 5xy + 25y^2) \]
Thus, the factored form of the expression \( x^3 + 125y^3 \) is:
\[ (x + 5y)(x^2 - 5xy + 25y^2) \]
Therefore, the correct response is:
(x + 5y)(x² - 5xy + 25y²).